Production of Quasicomposite Surface Layer of a Metal Material by Shock Wave Strain Hardening - A.V. Kirichek; D.L. Soloviev; A.Y. Altukhov (Журнал нано- та електронної фізики)
Quite often in order to improve the performance of a product it is necessary to form a strengthened structure that will be extremely hard and have good plasticity at the same time. One way to meet this challenge is to apply shock wave mechanical hardening to produce micro- or nanocrystalline heterogeneous structures in homogeneous metals or alloys. A peculiar feature of such structure is its layer-by-layer formation with smooth transition between hard and plastic areas, which improves the performance of the strengthened item significantly